Pre-recovery of fatty acid methyl ester (FAME) and anaerobic digestion as a biorefinery route to valorizing waste activated sludge. (August 2017) - Choi, Oh Kyung; Lee, Kwanhyoung; Park, Ki Young; Kim, Jae-Kon; Lee, Jae Woo
Abstract: This study presented the effects of lipids extraction from waste activated sludge (WAS) via in-situ transesterification on anaerobic digestion performance. The nonpolar transesterified product (TP) yield through the extraction was 9.68% of the dried mass of WAS and its fatty acid methyl esters (FAMEs) content was 78.45%. Pre-extraction of lipids lead to the solubilization of the sludge. The biochemical methane potential (BMP) test exhibited that both the extent and rate of methane production increased by 3.65 times after the pre-extraction of lipids. Overall solid reduction of WAS through the series of lipid extraction and anaerobic fermentation was enhanced by more than 5 times compared to that of control. Based on energy balance, the strategy proposed in this study could be an alternative biorefinery route to valorizing WAS with a simultaneous production of FAMEs as a biodiesel feedstock and biogas. Graphical abstract: Highlights: Lipid extraction as biodiesel FAME was achieved via transesterification of sludge. Lipid extraction lead to a significant solubilization of sludge. Solid reduction and methane production was enhanced in AD after pre-extraction. A strategy for co-recovery of biofuels from waste sludge was suggested and evaluated.